Production strategies for active heme-containing peroxidases from E. coli inclusion bodies – a review - Britta Eggenreich; Melissa Willim; David Johannes Wurm; Christoph Herwig; Oliver Spadiut (Biotechnology Reports, 2016)
Heme-containing peroxidases are frequently used in medical applications. However, these enzymes are still extracted from their native source, which leads to inadequate yields and a mixture of isoenzymes differing in glycosylation which limits subsequent enzyme applications. Thus, recombinant production of these enzymes in Escherichia coli is a reasonable alternative. Even though production yields are high, the product is frequently found as protein aggregates called inclusion bodies (IBs). These IBs have to be solubilized and laboriously refolded to obtain active enzyme. Unfortunately, refolding yields are still very low making the recombinant production of these enzymes in E. coli not competitive. Motivated by the high importance of that enzyme class, this review aims at providing a comprehensive summary of state-of-the-art strategies to obtain active peroxidases from IBs. Additionally, various refolding techniques, which have not yet been used for this enzyme class, are discussed to show alternative and potentially more efficient ways to obtain active peroxidases from E. coli.